Potensi Masalah Hukum Dalam Tanda Tangan Elektronik Dalam Pembuktian Hukum Acara Perdata Indonesia - Fauzi, Irvan; Rifai, Anis; Shebubakar, Arina Novizas (Fakultas Hukum, Universitas Boyolali, 2024)
Abstract Electronic signatures are currently often used on digital-based documents which basically can be said to be in the form of non-paper documents which can be debated in the process of proving civil procedural law because they are not in accordance with the types of evidence where the requirements are in physical form. Therefore the author raises issues such as what is the legal basis for the validity of electronic signatures in making agreements between parties in the technological era? how is the legal force of proving electronic signatures in Indonesian civil procedural law? The research method in this scientific journal uses a normative juridical approach using existing data through Open Source. The results of the research found that the legal basis for electronic signatures is regulated in the Electronic Transactions Act which provides a definition in the form of part of an electronic agreement for parties to agree together through the existence of an electronic system in preparing, analyzing, collecting, processing, storing , convey and be able to disseminate information electronically. Electronic signing as a form of electronic data on an agreement document in civil procedural law can be a potential problem if it is used as evidence in a proving trial process in court. Where electronic signing is a paperless transaction. This of course raises problems when the proof process is not in accordance with what is regulated in Article 1866 of the Civil Code, in this case it means that the evidence in the form of electronic data submitted is considered to have no legal force of proof, therefore it does not rule out the possibility that judges and other parties will reject it as evidence. Suggestions for the future are that the court can accommodate evidence in the form of electronic signatures. electronic data submitted is considered to have no legal force of proof, therefore it does not rule out the possibility that judges and other parties will reject it as evidence. Suggestions for the future are that the court can accommodate evidence in the form of electronic signatures Abstrak Tanda tangan elektronik saat ini sering dipakai pada dokumen yang berbasis digital yang pada dasarnya dapat dikatakan sebagai bentuk dari dokumen non-kertas yang dapat menjadi perdebatan dalam proses pembuktian hukum acara perdata karena tidak sesuai dengan jenis-jenis alat bukti yang mana persyaratannya dalam bentuk fisik. Oleh sebab itu penulis mengangkat permasalahan seperti bagaimanakah dasar hukum keabsahan dari tanda tangan elektronik dalam melakukan perjanjian antara para pihak di era teknologi? bagaimana kekuatan hukum pembuktian tanda tangan elektronik dalam hukum acara perdata Indonesia? Metode penelitian pada jurnal ilmiah ini menggunakan pendekatan yuridis normatif dengan memakai data-data yang ada melalui Open Source. Hasil dari penelitian menemukan dasar hukum dari tanda tangan elektronik diatur pada Undang-Undang Transaksi Elektronik yang memberikan definisi berupa bagian dari suatu perjanjian elektronik bagi para pihak secara bersama-sama untuk bersepakat melalui adanya sistem secara elektronik dalam mempersiapkan, menganalisis, mengumpulkan, mengolah, menyimpan, menyampaikan dan dapat untuk menyebarkan suatu informasi secara elektronik. Penandatanganan Elektronik sebagai bentuk dari data elektronik pada suatu dokumen perjanjian dalam hukum acara perdata ini dapat menjadi potensi masalah apabila digunakan sebagai bahan bukti di dalam sebuah proses persidangan pembuktian di pengadilan. Yang mana adanya penandatanganan secara elektronik merupakan transaksi tanpa kertas. Hal ini tentu menimbulkan permasalahan pada saat proses pembuktian yang tidak sesuai dengan yang diatur dalam pasal 1866 KUH Perdata, dalam hal ini berarti bukti berupa data elektronik yang diserahkan dianggap tidak memiliki kekuatan hukum pembuktian, oleh karenanya tidak menutup kemungkinan hakim dan pihak lain akan menolaknya sebagai alat bukti. Saran kedepannya agar pengadilan dapat mengakomodir alat bukti berupa tanda tangan elektronik.